Late-Onset Recurrent Femoral Cyst Formation 10 Years after ACL Reconstruction: A Case Report and Literature Review - Enrique Sanchez-Munoz; Antonio Maestro Fernández; Iván Pipa Muñiz; Nicolas Rodríguez García (Case Reports in Orthopedics)
Synovial fistula and cyst formation after anterior cruciate ligament (ACL) reconstruction is very unusual and almost always affects the tibia. Only 3 cases originating in the femur have been reported. We present a rare case of late-onset femoral cyst formation related to ACL reconstruction. Ten years after successful ACL reconstruction surgery, effusion and pain at the lateral aspect of the lateral femoral condyle appeared. Symptoms persisted despite initial percutaneous drainage and conservative treatment. Surgery was carried out, with drainage and graft-fixation pin device removal, with recurrent cyst formation after the intervention. Total recovery of the patient was achieved after carrying out revision surgery consisting in bone tunnel filling using autologous bone graft and occlusion of cortical bone defect with local fascial flap. The development of this unusual complication was related to lack of absorption of the fixation device, bone burn due to drilling, and persistent synovial fluid in the femoral bone tunnel, combined with the absence of bone ingrowth.